Gas hydrate distributions in sediments of pockmarks from the Nigerian margin – Results and interpretation from shallow drilling. (January 2015) - Wei, Jiangong; Pape, Thomas; Sultan, Nabil; Colliat, Jean-Louis; Himmler, Tobias; Ruffine, Livio; de Prunelé, Alexis; Dennielou, Bernard; Garziglia, Sebastien; Marsset, Tania; Peters, Carl A.; Rabiu, Abdulkarim; et al.
Abstract: A joint research expedition between the French IFREMER and the German MARUM was conducted in 2011 using the R/V 'Pourquoi pas?' to study gas hydrate distributions in a pockmark field (1141–1199 m below sea surface) at the continental margin of Nigeria. The seafloor drill rig MeBo of MARUM was used to recover sediments as deep as 56.74 m below seafloor. The presence of gas hydrates in specific core sections was deduced from temperature anomalies recorded during continuous records of infrared thermal scanning and anomalies in pore water chloride concentrations. In situ sediment temperature measurements showed elevated geothermal gradients of up to 258 °C/km in the center of the so-called pockmark A which is up to 4.6 times higher than that in the background sediment (72 °C/km). The gas hydrate distribution and thermal regime in the pockmark are largely controlled by the intensity, periodicity and direction of fluid flow. The joint interaction between fluid flow, gas hydrate formation and dissolution, and the thermal regime governs pockmark formation and evolution on the Nigerian continental margin. Highlights: Pockmarks on the Nigerian continental margin were investigated for gas hydrates. Long sediment cores were recovered with the portable MeBo drill rig. Infrared and pore water chloride measurements revealed gas hydrate distributions. Geothermal gradients in the pockmark center up to five fold higher than at the rim. Fluid flow and gas hydrate dynamics influence the evolution of pockmarks.